Wind-remobilisation processes of volcanic ash. Consensual Document - Bonadonna, Costanza (2020)
24 páginas. | Documento de consenso del "Workshop on Wind-remobilisation processes of volcanic ash", San Carlos de Bariloche, Argentina, 23-26 October 2019.